Environmental Health - Grandjean, Philippe; Ozonoff, David; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Environmental Health publishes manuscripts on all aspects of environmental and occupational medicine and related studies in toxicology and epidemiology. The journal is aimed at scientists and practitioners in all areas of environmental science where human health and well-being are involved, either directly or indirectly. Environmental Health is a public health journal serving the public health community and scientists working on matters of public health interest and importance pertaining to the environment.
Keywords: Environment; Public health; Occupational medicine; Environmental health; Environment; Environmental Health; Occupational Medicine/Industrial Medicine; Public Health